O8 The COMPOSE Study: Characteristics, Outcomes and Management of PeriprOsthetic fractures: a Service Evaluation. (8th April 2021) - Scrimshire, A B; Farrier, A; Kottam, L; Walker, R; Jameson, S; Baker, P; Scrimshire, Ashley
Abstract: Introduction: The number of peri-prosthetic fractures (PPF) is increasing, yet there still lacks a clear evidence-based strategy to best manage these injuries. There is a growing interest to collect a substantial body of information about PPFs in order to aid understanding of this population, current treatments and clinical outcomes. COMPOSE is a national multi-centre, retrospective service evaluation examining the incidence, management, outcomes and patient characteristics of those presenting to secondary care hospitals in the UK with a PPF. Methods: Data will be collected via REDCap for all PPFs which presented to the orthopaedic departments between 1st January 2018 to 31st December 2018 from the participating hospitals. The evaluation will aim to collect pre-operative data (baseline demographics, fracture characteristics, surgical characteristics) and post-operative outcome data (length of stay, discharge, post-operative complications, re-admissions, re-operations, mortality). Results: Currently, 24 hospital sites have registered with a total of 388 cases recorded. We continue to seek further interested sites to join. COMPOSE will generate a unique and robust dataset of PPFs and current practices. All data and outcomes will be reported descriptively. The outcome measures will be analysed using regression modelling with adjustment for baseline variables. Between group comparisons will be reported using confidence intervals and p-values. Conclusion: Following analysis, the aim is to make supported recommendations regarding management, to help plan clinical services for this patient population and to assist with identification of potential risk factors for PPFs and the subsequent outcomes. The dataset will also aid development of testable hypotheses for future research.